A study of conservative management of tibial plateau fractures - Shrestha, Robin; Kandel, Manoj; Gupta, Hemant Kumar; Shrestha, Sundar Kumar; Dongol, Sagun; Hamal, Rajkumar Ravi (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Tibial plateau fractures have been studied and reported extensively and exhaustively but still controversy exists over its management, whether surgical or conservative. Although several methods of treatment have been devised, each method of treatment offers their own advantages and disadvantages. In this study we utilized conservative method which like any other mode of treatment restores articular congruity, axial alignment, joint stability, functional motion and avoids complications. This study was conducted with an objective to evaluate the functional and radiological outcome of conservative treatment. Materials & Methods: Forty two randomly selected cases of tibial plateau fracture in adults more than 20 years of age were treated with above knee plaster of Paris cast for 4 to 6 weeks. At the end of six months outcome of this study was analyzed by Modified Rasmussen clinical criteria and radiological evaluation. Results: The Clinical assessment showed that 48% had excellent, 28% had good, 10% had fair and 14% had poor outcome while radiological outcome of this study showed 40.5% excellent, 33.3% fair, 9.5% fair and 16.7% poor result. Conclusion: In appropriately selected cases conservative treatment is a reliable alternative and is certainly without the complications associated with surgery. JCMS Nepal. 2016;12(1):5-9.